PENGARUH KOMPENSASI DAN FLEKSIBILITAS KERJA TERHADAP KEPUASAN KERJA PEKERJA NON-KONVENSIONAL DI TANGERANG SELATAN PADA ERA DIGITAL - Maheswari, Deswita; Utama, Rony Edward (Media Riset Bisnis Ekonomi Sains dan Terapan, 2026)
The rapid growth of the digital era has created non-conventional jobs characterized by flexible work arrangements and different compensation systems from traditional employment. However, research on job satisfaction among non-conventional workers remains limited. This study examines the effect of compensation and work flexibility on job satisfaction of non-conventional workers in South Tangerang. Using a quantitative associative design, data were collected from 96 respondents selected through probability sampling based on the Cochran formula. Questionnaires were analyzed using multiple linear regression. The findings show that compensation and work flexibility have a positive and significant effect on job satisfaction, both partially and simultaneously. These results provide practical insights for companies and digital platforms in developing effective compensation and flexible work policies to improve job satisfaction in the digital era.Keywords: Compensation, Work Flexibility, Job Satisfaction